Bali Diaspora di Jayapura: Makna Pura Agung Surya Bhuvana dalam Membangun Kerukunan di Tanah Papua - I Wayan Rai S; I Gusti Made Sunartha; Ida Ayu Made Purnamaningsih; Ni Made Ruastiti; Yunus Wafom (Jurnal Kajian Bali (Journal of Bali Studies), 2020)
The purpose of this study is to look for the meanings of the Balinese temple Pura Agung Surya Bhuvana in Jayapura in building harmony in the land of Papua. The life of Jayapura people is identical with the frequent riots. It looks different from the life of the Balinese diaspora around the temple Surya Bhuvana which marked by inter-religious harmony. The study focused on two issues: Why do non-Hindus in Jayapura often visit the Pura Agung Surya Bhuvana? How do they understand the temple Surya Bhuvana in this global era? This is a qualitative research and data were collected through observation, interview, FGD, and document study techniques. Data were analyzed with religious theory, symbol theory, and structural-functional theory. The results showed that the hospitality of the Balinese diaspora who manages the temple makes non-Hindus community feel welcome to visit the temple. The Balinese diaspora community in Jayapura interpreted Pura Agung Surya Bhuvana as a place of worship, a meeting place for people of different faiths, a place of art, a place to strengthen multi-cultural life and as a medium to strengthen national integration.